ACTH Action on Messenger RNA Stability Mechanisms - Desroches-Castan, Agnès; Feige, Jean-Jacques; Cherradi, Nadia (Frontiers in Endocrinology, 2017)
The regulation of mRNA stability has emerged as a critical control step in dynamic gene expression. This process occurs in response to modifications of the cellular environment, including hormonal variations, and regulates the expression of subsets of proteins whose levels need to be rapidly adjusted. Modulation of messenger RNA stability is usually mediated by stabilizing or destabilizing RNA-binding proteins (RNA-BP) that bind to the 3’-untranslated region (3’UTR) regulatory motifs, such as AU-rich elements (AREs). Destabilizing ARE-binding proteins enhance the decay of their target transcripts by recruiting the mRNA decay machineries. Failure of such mechanisms, in particular misexpression of RNA-BP, has been linked to several human diseases. In the adrenal cortex, the expression and activity of mRNA stability regulatory proteins are still understudied. However, ACTH- or cAMP-elicited changes in the expression/phosphorylation status of the major mRNA-destabilizing protein TIS11b/BRF1 or in the subcellular localization of the stabilizing protein HuR have been reported. They suggest that this level of regulation of gene expression is also important in endocrinology.